Intraperitoneal hemorrhage following primary cytoreductive surgery for ovarian cancer: Successful treatment with superior epigastric artery embolization: A rare case of superior epigastric artery injury - Capozzi, Vito Andrea; Butera, Diana; Armano, Giulia; Gaiano, Michela; Monfardini, Luciano; Gambino, Giulia; Cianciolo, Alessandra; Paladini, Ilaria; Epifani, Enrico; Berretta, Roberto (Acta Biomedica Atenei Parmensis, 2021)
Hemoperitoneum often occurs due to abdominal trauma, abdominal tumors, gastro-intestinal perforation and more rarely it’s spontaneous due to coagulopathies. Superior epigastric artery (SEA) iatrogenic damage is rarer than the Inferior epigastric artery injury, it may occur during laparotomy and, in most cases, it causes a rectus muscle hematoma. We present the case of a caucasian 44 years-old-woman with hemoperitoneum after cytoreductive surgery for ovarian cancer. Active bleeding from the distal branch of the SEA was diagnosed at computed tomography and coil embolization followed by surgical laparotomic drainage of the hemoperitoneum was performed. After initial resolution, active bleeding from the same vessel was observed. Further embolization of the same vessel was necessary to stop bleeding. Ultrasound follow-up showed a complete resolution of the hemoperitoneum